Warm congratulations on IJABE’s inclusion in Ei Compendex - Yingkuan, Wang (International Journal of Agricultural and Biological Engineering, 2013)
IJABE has recently been included for abstracting and indexing in Ei Compendex after strict peer review and evaluation by the Compendex Scope and Coverage Committee. Warm congratulations on IJABE's coverage in Ei Compendex!